The coffee scene in Glasgow's West End: On the class practices of the new urban middle classes. (June 2019) - Shaker, Reza; Rath, Jan
Abstract: The shift from Fordism to Post-Fordism has led to the emergence of new socioeconomic arrangements as well as the proliferation of new urban cultural forms. These developments have coincided with gentrification and the arrival of the new middle classes in inner-city neighbourhoods resulting in the emergence of new consumption spaces and new urban cultures. Focusing on Glasgow's West End with a vibrant urban scene, this paper explores some characteristics of the new urban middle classes and their motivations for frequenting and patronising new urban consumption scenes. Drawn on a case study of specialty coffee bars, the study argues that specialty coffee consumers through their everyday consumption preferences and sharing a set of ethical dispositions and cultural practices, subjectively and objectively define and demarcate their sense of class. Highlights: The new urban middle classes subjectively and objectively define and demarcate their sense of class through consumption. They employ lifestyle goods and commodities and gravitate towards certain urban consumption spaces. Although highly differentiated, by employing different forms of human capital, they share a set of qualities and practices.